Increased prevalence of posttraumatic stress disorder in patients after transient ischemic attack - Kiphuth, Ines C.; Utz, Kathrin S.; Noble, Adam J.; Köhrmann, Martin; Schenk, Thomas (Stroke, 2014)
A transient ischemic attack (TIA) involves temporary neurological symptoms but leaves a patient symptom-free. Patients are faced with an increased risk for future stroke, and the manifestation of the TIA itself might be experienced as traumatizing. We aimed to investigate the prevalence of posttraumatic stress disorder (PTSD) after TIA and its relation to patients' psychosocial outcome.Patients with TIA were prospectively studied, and 3 months after the diagnosis, PTSD, anxiety, depression, quality of life, coping strategies, and medical knowledge were assessed via self-rating instruments.Of 211 patients with TIA, data of 108 patients were complete and only those are reported. Thirty-two (29.6%) patients were classified as having PTSD. This rate is 10× as high as in the general German population. Patients with TIA with PTSD were more likely to show signs of anxiety and depression. PTSD was associated with the use of maladaptive coping strategies, subjectively rated high stroke risk, as well as with younger age. Finally, PTSD and anxiety were associated with decreased mental quality of life.The experience of TIA increases the risk for PTSD and associated anxiety, depression, and reduced mental quality of life. Because a maladaptive coping style and a subjectively overestimated stroke risk seem to play a crucial role in this adverse progression, the training of adaptive coping strategies and cautious briefing about the realistic stroke risk associated with TIA might be a promising approach. Despite the great loss of patients to follow-up, the results indicate that PTSD after TIA requires increased attention.
EVALuna2:22311